The learning curve of endoscopic endonasal transsphenoidal surgery for pituitary adenomas with different surgical complexity - Huang, Jinxiang; Hong, Xinjie; Cai, Zheng; Lv, Qian; Jiang, Ying; Dai, Wei; Hu, Guohan; Yan, Yong; Chen, Juxiang; Ding, Xuehua (Frontiers in Surgery, 2023)
Objective: To investigate the learning curve under different surgical complexity in endoscopic transsphenoidal approach for pituitary adenoma. Methods: We retrospectively collected 273 pituitary adenoma cases treated by endoscopic transsphenoidal surgery from December 2014 to August 2021 in our single center. We evaluated the temporal trends in operative time, gross total resection rate, biochemical cure rate, and perioperative cerebral spinal fluid leakage. Results: The median operative time decrease from 169 to 147 minutes across the three periods (P=0.001). A significant decrease in operative time was only seen in the simple groups [Knosp grade 0-2 adenoma (169 to 137 minutes, P＜0.001), macroadenoma (166 to 140 minutes, P＜0.001) and first operation (170.5 to 134 minutes, P＜0.001)] but not in their complex counterparts (P＞0.05). GTR rate increased from 51.6% to 69.2% (P=0.04). Surgical period was an independent factor for GTR only in the simple groups [Knosp grade 0-2 adenoma: OR 2.076 (95%CI 1.118-3.858, P=0.021); macroadenoma: OR=2.090 (95%CI 1.287-3.393, P=0.003); first operation: OR=1.809 (95%CI 1.104-2.966, P=0.019)] but not in the complex groups. No clear temporal trend was seen in biochemical cure rate (from 37.5% to 56.3%, P=0.181). Although intraoperative CSF leakage rose (from 20.9% to 35.2%) and postoperative CSF leakage reduced (from 12.1% to 5.5%), there was no statistically significant trend across the three time periods (P＞0.05). Conclusion: This study showed the learning curves for different surgical complexity. Differentiating surgical difficulty and using multivariate combined analysis may be more helpful in clinical practice.